Hubungan Strategi Koping dengan Kecemasan Mahasiswa dalam Mengerjakan Skripsi - Martha, Fhirlynesia; Ardi, Zadrian (MASALIQ, 2024)
This study aims to describe coping strategies and anxiety among students in writing their theses and to identify the relationship between coping strategies and anxiety among students in writing their theses at Universitas Negeri Padang. This research is a descriptive correlational quantitative study. The research sample consisted of 248 final-year students selected using the Proportional Stratified Random Sampling method. Data were obtained using validated and reliable coping and anxiety questionnaires. Data processing was carried out using percentage analysis techniques, and the relationship between variables was tested using the Pearson product-moment correlation formula. The results of this study indicate that: (1) The level of coping strategies among students is in the moderate category, with a percentage reaching 71%. (2) The level of anxiety among students is in the high category, with a percentage reaching 87%. (3) Correlation analysis shows a negative and significant relationship between coping strategies (variable X) and the level of anxiety (variable Y) among students, with a correlation coefficient (r) of -0,559 and a significance level of 0.000, indicating a fairly strong relationship between the two variables. This significant negative relationship suggests that the higher the level of coping strategies, the lower the level of anxiety among students, and conversely, the lower the coping strategies, the higher the anxiety level among students.